Health and Safety Education in Auto Body Collision and Machine Tool Technology Programs in Vocational Colleges: Challenges and Opportunities. (13th September 2018) - Bejan, Anca; Parker, David L; Skan, Maryellen; Xi, Min
Abstract: Collision repair, machining, and metal manufacturing are industries with a large percentage of small businesses whose owners face unique challenges implementing health and safety regulatory requirements. Previous research found that 72% of collision repair technicians and 47% of machinists attended some classes or graduated from vocational colleges. Although health and safety is a mandatory part of the curricula for post-secondary vocational education, little is known about what, how, and when health and safety is taught and if teaching is effective. Surveys and discussion groups were used to evaluate health and safety education in two vocational colleges in Minnesota. Six instructors and 76 students in collision repair, and 6 instructors and 130 students in machine tool technology programs participated. Instructors had no formal training in health and safety, few teaching materials, and lacked opportunities to learn about safety in their trade. Teaching was unscripted and heavily influenced by each instructor's™ industry experience, knowledge, perceptions and attitude towards safety, with little or no guidance from school administration, or safety professionals. Student survey results show that graduates have significant gaps in safety and health knowledge. Standardized trade-specific curricula and instructor training are needed to ensure students receive adequate health and safety education.